Aquaculture’s struggle for space: the need for coastal spatial planning and the potential benefits of Allocated Zones for Aquaculture (AZAs) to avoid conflict and promote sustainability - P Sanchez-Jerez (Inter-Research, 2016)
Aquaculture is an increasingly important food-producing sector, providing protein for human consumption. However, marine aquaculture often struggles for space due to the crowded nature of human activities in many marine coastal areas, and because of limited attention from spatial planning managers. Here, we assess the need for coastal spatial planning, emphasising the establishment of suitable areas for the development of marine aquaculture, termed Allocated Zones for Aquaculture (AZAs), in which aquaculture has secured use and priority over other activities, and where potential adverse environmental impacts and negative interactions with other users are minimised or avoided. We review existing examples of marine aquaculture spatial development worldwide and discuss the proper use of site selection in relation to different legal and regulatory requirements. National or regional authorities in charge of coastal zone management should carry out spatial planning defining optimal sites for aquaculture to promote development of sustainable marine aquaculture and avoid conflict with other users, following a participatory approach and adhering to the principles of ecosystem-based management.